Income Inequality in Armenia : Drivers, Challenges, and Policy Implications - Movsesian, Roman (2025)
The objective of this thesis is to examine the causes and dynamics of income inequality in Armenia since its independence in 1991 with a focus on the applicability of the Kuznets curve and neoliberal economic theory that will help to explain the evolution of income inequality during Armenia’s transition from a centrally planned to a market economy. Macroeconomic indicators such as the Gini coefficient, Palma ratio, Lorenz curve, and other measurements, as well as policy developments and structural reforms, were analyzed to verify if the country followed the U-shaped curve proposed by the Kuznets theory and the influence of neoliberalist reforms. The analysis shows that, although some positive changes have been observed, income gaps remain significant and are even widening due to underfunding of social programs, a rigid tax system, and existing interregional disparities. The study presents evidence-based recommendations on key public policy issues, including the introduction of progressive taxation, strengthening social support, education reform, and adaptation to labor market transformations, all of which are necessary to reduce inequality and stimulate sustainable, inclusive development.